Essure Microinsert Abdominal Migration after Hysteroscopic Tubal Sterilization of an Appropriately Placed Essure Device: Dual Case Reports and Review of the Literature - Shadi Rezai; Meghan LaBine; Hunter Azdel Gomez Roberts; Isamarie Lora Alcantara; Cassandra E. Henderson; Malvina Elmadjian; Dilfuza Nuritdinova (Case Reports in Obstetrics and Gynecology)
Background. The Essure device is a method of permanent sterilization widely used in the US that has proven to be safe and effective in most cases. However, there have been reports of device migration that have led to failed tubal occlusion as well as several other serious complications resulting from the presence of the device in the abdominal cavity. Case. This paper represents two cases of failed tubal occlusion by an appropriately placed Essure device without signs or symptoms of further complications related to device migration. Conclusion. Although there have only been 13 reported cases of abdominal device migration since November 2014, this case indicates that the actual number may be higher than reported since it is possible for migration to occur without additional complications. In the majority of reported cases of abdominal migration a major complication requiring surgical correction occurred, such as adhesions, small bowel obstruction, bowel perforation, or persistent pelvic pain. To avoid these complications it is recommended that migrating implants be removed; however, this case also represents an example of when a migrating device may remain in situ in an asymptomatic patient.